Putting ethics and economic rationality together: an Aristotelian and philosophical approach. (18th September 2014) - Queiroz, Regina Maria da Cruz
<x xml:space="preserve">Abstract</x> The gap between economic rationality, as embedded in utility maximization, and ethical rationality, identified with a set of rules that prescribe the right course of action, has been a challenging issue for economists, philosophers, and business ethicists. Despite the difference and the noncompetition between a scientific economic approach of economics and business ethics, and a behavioral and philosophical one, we highlight the importance of the Aristotelian concept of prudence or phronesis applied to business activity. Phronesis allows for a conceptualization of rationality that can be simultaneously applied to economics and ethics. It also allows conceiving the intrinsically ethical nature of economic rationality. This relationship requires an appropriate education and the intervention of the state.